Meningkatkan Manajemen Persediaan Suku Cadang (Sparepart) Motor pada Bengkel Tiga Putra di Bojonegara Banten - Ferdy Apriyansah; Ifan Ramadhan; Nurul Fawaz; Saefudin Saefudin (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
Tiga Putra's workshop, which is located in Bojonegara Banten, still has meetings with the large number of requests for vehicle repairs from customers, making the workshop have to provide various kinds of spare parts. The purpose of making this journal is to find out the existing conditions in the three sons' workshop and we provide solutions on how to increase the supply of spare parts. The aim of increasing the inventory of motorbike spare parts is to ensure the availability of components needed for vehicle maintenance and repair, so as to increase operational efficiency and customer satisfaction. The methodology used is a qualitative case study, with data collection through in-depth interviews, documentation studies and field observations. The results of the research are that there are obstacles in increasing the supply of motorbike spare parts, namely limited resources, be it money, time or labor. And Tiga Putra's workshop also has a strategy to increase spare parts inventory which can help with real-time inventory and plan reorders more efficiently. And there is also a spare parts inventory table so you can find out which spare parts orders are sold out within one year and require delivery.